THE INCREASE OF TITANIUM IMPLANTS OSTEOINTEGRATIVE PROPERTIES BY USING SYNTHETIC BIOACTIVE CALCIUM-PHOSPHATE MINERAL COMPLEX - A. A. Markov (Современная наука и инновации)
The possibility of increasing the osseointegration properties of titanium implants using a coating based on a synthetic bioactive calci-um-phosphate mineral complex is presented.